Dietary Fat Reduction Behaviors among African American, American Indian, and White Older Adults with Diabetes - Quandt, Sara A. (2009)
Dietary self-management of diabetes is often difficult for older adults to practice, particularly in rural communities. We describe patterns and correlates of dietary fat reduction among older rural adults with diabetes of any type. In-home interviews were conducted with a multiethnic random sample of 701 adults ≥65 with diabetes from two North Carolina counties. The Fat and Fiber Behavior Questionnaire was used to measure dietary behaviors. Separate multiple linear regressions assessed effects of gender, ethnicity, and diabetes education. In general, scores were more favorable for practices that involved modifying food preparation (e.g., avoiding frying) and less favorable for practices that involved changing foods consumed (e.g., substituting fruits and vegetables as desserts or snacks). American Indians and African Americans had less favorable scores than whites, and diabetes education was associated with greater fat restriction for women than men. Older men and ethnic minorities with diabetes should be targeted for dietary change education.